DNA barcoding in Nautilus pompilius (Mollusca:Cephalopoda): Evolutionary divergence of an ancient species in modern times - Williams, R.; Newman, Stephen; Sinclair, W. (2012)
DNA barcoding studies to elucidate the evolutionary and dispersal history of the current populations of Nautilus pompilius allow us to develop a greater understanding of their biology, their movement and the systematic relationships between different groups. Phylogenetic analyses were conducted on Australian N. pompilius, and COI sequences were generated for 98 discrete accessions. Sequences from samples collected across the distribution were sourced from GenBank and included in the analyses. Maximum likelihood revealed three distinct clades for N. pompilius: (1) populations sourced from west Australia, Indonesia and the Philippines; (2) populations collected from east Australia and Papua New Guinea; (3) western Pacific accessions from Vanuatu, American Samoa and Fiji, supporting previous findings on the evolutionary divergence of N. pompilius. A minimum spanning tree revealed 49 discrete haplotypes for the 128 accessions, from a total of 16 discrete sampling locations. Population similarity reflects oceanic topographic features, with divergence between populations across the N. pompilius range mirroring geographical separation. This illustrates the success of DNA barcoding as a tool to identify geographic origin, and looks to the future role of such technology in population genetics and evolutionary biology. © CSIRO 2012 .